PTU-007 Development Of A Smartphone App To Aid The Clinical Management Of Polyposis Syndromes. (9th June 2014) - Lee, GH; Latchford, A; Phillips, RK; Clark, SK
Abstract : Introduction: Smartphone "apps" are becoming increasingly used by health care professionals (HCPs) as a quick and easy guide for delivering evidence-based medicine. "Apps" are particularly effective in providing guidelines accessible from a smartphone with contents that can be updated frequently. The Polyposis Registry at our institution has spearheaded the formulation of guidelines for the management of inherited polyposis syndromes. We set out to develop these into "app" form. Methods: Essential content of our institution's guidelines (based on published guidelines) was selected by a multidisciplinary team and edited to suitable format for the "app" programmers, and a trial version was produced. This was tested by a group of HCPs (colorectal surgeons, gastroenterologists, nurse specialists). A questionnaire was sent out after the trial to determine the usefulness and effectiveness of the "app". Results: Eighteen HCPs trialled the "app". 89% found it relevant and useful in their clinical practice, and would use it at least once a month. 83% said that it provided the information they required, and all would recommend it to a colleague. None considered it hard to use. Some improvements were suggested, which will be implemented in the final version offered externally. Conclusion: We present an "app" which provides our evidence-based guidelines for the management of polyposis syndromes in an easily accessible and updatable form, and describe its development. Disclosure of Interest: None Declared.